Evaluasi Sistem Penilaian Kinerja Karyawan Dalam Meningkatkan Produktivitas Karyawan Di Rumah Sakit X Jombang - Ellawati Sri Puspitasari; Nur Hidayah; Sri Handari Wahyuningsih (Program Studi Magister Manajemen Rumah Sakit, Jenjang Pasca Sarjana (S2), Pasca Sarjana Universitas Muhammadiyah Yogyakarta, 2018)
X Jombang Hospital is a type D hospital with 203 employees. Human resources are an important element in organizing the organization. One way to optimize the work of human resources is to conduct periodic performance appraisals. Currently performance appraisals are only routinely implemented for career hikes. While the performance appraisal of employees still can not be done routinely every 1 year. The results of the assessment also can not show the actual performance of employees. A subjective assessment and an unfair sense of judgment can have a negative impact on both employees and the hospital. This phenomenon requires an evaluation of the performance appraisal sistem in the hope of improving employee performance and productivity. Based on the type of research included in qualitative descriptive research. The population used is permanent employees at Jombang Islamic Hospital of 68 people. Based on the results of the study showed assessment of employee performance that has been done at X Islamic Hospital is considered not effective. Employees are of the opinion that performance appraisals already have good indicators, but the results are still not yet objective to describe actual employee performance. Revisions to the employee performance appraisal form (the questionnaire) and the addition of performance performance indicators need to be done as well as the performance appraisal results need to be gained follow-up.